2013
DOI: 10.1186/1471-2180-13-280
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and molecular characterization of Treponema phagedenis-like spirochetes isolated from a bovine digital dermatitis lesion

Abstract: BackgroundBovine papillomatous digital dermatitis (DD) is the leading cause of lameness in dairy cattle and represents a serious welfare and economic burden. Found primarily in high production dairy cattle worldwide, DD is characterized by the development of an often painful red, raw ulcerative or papillomatous lesion frequently located near the interdigital cleft and above the bulbs of the heel. While the exact etiology is unknown, several spirochete species have been isolated from lesion material. Four isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 41 publications
2
39
0
Order By: Relevance
“…The enzyme pattern of reactivity of current isolates with positive results for esterase C4, esterase lipase C8, leucine arylamidase, trypsin, and chymotrypsin (group I isolates) was similar to UK bovine treponemes of group 3 and T. pedis except for leucine arylamidase (Evans et al, 2008 and2009a, respectively). Group II isolates shared similar reactivity with T. phagedenis Kazan except for β-galactosidase (Wilson-Welder et al, 2013). The enzyme profiles of the current isolates produced a specific pattern that differed from the genus Treponema shown in Table 4.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The enzyme pattern of reactivity of current isolates with positive results for esterase C4, esterase lipase C8, leucine arylamidase, trypsin, and chymotrypsin (group I isolates) was similar to UK bovine treponemes of group 3 and T. pedis except for leucine arylamidase (Evans et al, 2008 and2009a, respectively). Group II isolates shared similar reactivity with T. phagedenis Kazan except for β-galactosidase (Wilson-Welder et al, 2013). The enzyme profiles of the current isolates produced a specific pattern that differed from the genus Treponema shown in Table 4.…”
Section: Discussionmentioning
confidence: 83%
“…Although Holstein or Friesian-Holstein cows form the backbone of the dairy industry worldwide, managed usually in larger herds and housed partially or permanently throughout the year, Simmen- Table 2. Bacterial size and flagella number of treponemes identified in this study, compared with Treponema pedis and Treponema phagedenis characteristics described by Evans et al (2008) and Wilson-Welder et al (2013) Treponeme and numbers examined (n) (Evans et al, 2008) 3:6:3 5:10:5 5 16 0.2 0.3 Reference for T. phagedenis (Wilson-Welder et al, 2013) 7:14:7 9:18:9 8 9.7 0.3 0.35 Figure 3. Neighbor-joining phylogenetic tree with respect to 16S rRNA gene sequence comparisons of ~1,400 aligned bases (TOVAG112O888 in this study).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Studies have shown that T. phagedenis migrates intercellularly deep within the epidermis and, if left untreated, digital dermatitis lesions eventually affect the whole hoof (52,53). Recent biochemical, molecular, and physiological characterizations, together with genome-wide comparisons of T. phagedenis strain F0421 and bovine T. phagedenis isolates (including strain 4A), indicated that the two spirochetes are almost identical in terms of biochemistry and genetics, leading to the conclusion that these bacteria belong to the same species and that the current description of T. phagedenis should be broadened to include both commensal strains of humans and pathogenic strains in cattle (54).…”
Section: Discussionmentioning
confidence: 99%
“…The ruminal environment may favor the survival of certain treponemes, because an environment rich in volatile fatty acids favors T. phagedenis (21). Further, the ability of treponemes to colonize different environments depends, among other factors, on the presence of periplasmic flagella for better propulsion through highly viscous or viscoelastic material (22), such as ruminal fluid and humid claw skin.…”
mentioning
confidence: 99%